PENERAPAN STRATEGI PEMBELAJARAN UNTUK MENINGKATKAN MINAT MEMBACA SISWA - Umi Fitri Lestari; M. Dwi Rahman Sahbana; Syaiful Dinata; Yelykha Henirayuza Nst; Fatoni Achmad; Mar’atun Sholiha; Mowafg Abrahem Masuwd (At Turots: Jurnal Pendidikan Islam, 2025)
This study aims to increase reading interest and strengthen moral values ​​in students of SMPN 3 Tempuling through a learning approach using illustrated fairy tales and folk tales. This strategy was designed in response to the low literacy skills and weak character building in elementary school students in rural areas. This study used the Classroom Action Research (CAR) approach model Kemmis and McTaggart which consists of four cycles: planning, action implementation, observation, and reflection. The results of the implementation showed that the application of illustrated fairy tales and local folk tales was able to significantly increase students' interest in reading, including those who were not previously fluent readers. Reading interest scores increased between 20% and 44%. The visualized stories were also able to evoke emotional responses in students and instill character values ​​such as honesty, empathy, responsibility, and cooperation. This strategy is considered appropriate to the local socio-cultural context and able to reach all students comprehensively and inclusively. Therefore, this local story and visual media is recommended as an alternative learning approach to develop literacy and character at the elementary school level.